2023
DOI: 10.3390/children10040721
|View full text |Cite
|
Sign up to set email alerts
|

Maturity-Related Variations in Morphology, Body Composition, and Somatotype Features among Young Male Football Players

Abstract: The study aimed to investigate differences in anthropometry, body composition (BC), and somatotype in young football players of the same chronological age according to the maturity stage. Overall, 64 elite players (age: 14.28 ± 0.46 years) were evaluated for standing and sitting body height, girth measures, and BC using the bioelectric impedance scale and skinfold thickness. In total, two-thirds (73.44%, n = 47) of football players were classified as on-time maturers, 12.50% (n = 8) were early maturing, and 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Fitness score differences do not compromise primary study results concerning the relations between playing position, morphology, and athleticism. It is important to consider the clinical relevance of even slight differences in age due to biological development as with single test performance ( 46 ), maturity has a significant similar impact on athleticism scores, respectively. Physical and physiological factors linked to both maturity and chronological age significantly impact an individual's athletic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Fitness score differences do not compromise primary study results concerning the relations between playing position, morphology, and athleticism. It is important to consider the clinical relevance of even slight differences in age due to biological development as with single test performance ( 46 ), maturity has a significant similar impact on athleticism scores, respectively. Physical and physiological factors linked to both maturity and chronological age significantly impact an individual's athletic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the authors concluded that HIIT is not superior to constant intensity endurance training (CIET) in improving aerobic or anaerobic parameters in adolescents. The research regarding the importance of SSG on the optimization of sports performance in sports games in general [54][55][56][57][58], and in football in particular, is numerous, as is made evident by their positive impact on psychological, physical, tactical and technical skills in the sports training process and in competitive games, for all age groups [59][60][61][62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%